The story behind the storyteller a study on content creators' journeys in making infant care resources - Reyes, Marnie Joy C.; Jamero, Josephine Louise (Quezon City University of the Philippines Diliman, 2025)
New parents are driven by a desire to provide their infants with the best possible start in life and prioritize optimal care in this critical stage of development. With the emergence of increasing resources of parenting and health-related guidance on social media, parents have turned to these avenues when making crucial decisions about infant care. A gap exists, however, where little to no studies have delved into the narratives of the content creators behind the online infant care resources (ICR). Using neo-ecological theory as a lens to organize, analyze, and process data, this study aimed to determine the narratives of four (4) content creators in their journeys in making ICR. Despite their unique personal journeys, common themes emerged regarding their motivations, challenges, and successes. Results also show that there is an interplay of factors in the development of content creators as persons and as professionals. Their person characteristics, physical and virtual microsystems, as well as the positive and inverse proximal processes in their environment all played a role in their content creation pursuits and perceived successes. Findings from this study reveal essential information for building a deeper understanding of the digital ecosystem related to infant care. This knowledge can inform better support strategies and foster a collaborative and informed online community for content creators and families.
In partial fulfillment for the Degree of Master of Family Life and Child Development
Thesis
Keywords: Parents -- Psychology; Infants -- Care; Parenting -- Philippines; Social media -- Influence; Infant Care Resources (ICR).; PPCT Model; Neoecological Theory; Content creators